Relationship between protein deficiency accompanied by low body mass index with the head shape and face type of 6-7 years old children - Gunawan, Idelia; Andiesta, Niekla Survia; Gartika, Meirina; Primarti, Risti Saptarini (Faculty of Dentistry Universitas Padjadjaran, 2020)
Introduction: Environmental factors such as socio-economic and nutrients factor can affect the dimensions and proportions of the body. Nutritional intake has a long-term effect on physical growth and can be assessed through body mass index up to age. Children with a nutritional disorder are characterised with low body mass index. This study was aimed to analyse the relationship of protein deficiency and low body mass index on the head shape and facial type of 6-7 years old children. Methods: The research type was descriptive correlative, and the research was conducted towards 16 subjects with low body mass index. Protein deficiency was assessed from food intake for 3 x 24 hours through food recall method and interview. The measurement of the cephalic and facial index was carried out to find out the head shape and face type, and then to correlate with protein deficiency and body mass index. Data was analysed using the chi-square test with the significance (p-value)<0.05. Results: There was a significant correlation between protein deficiency and low body mass index with the head shape (p-value=0.007), and the facial type of 6-7 years old children (p-value=0.027). There was a significant correlation between head shape with facial type in protein-deficient children with low body mass index (p-value=0). Conclusion: Protein deficiency accompanied by low body mass index influences the head shape and facial type of children.